Immunohistochemical Reappraisal Regarding the Frequency of Primary Salivary Gland Follicular Lymphoma. (February 2019) - Itami, Hiroe; Nakamine, Hirokazu; Takeda, Maiko; Nakai, Tokiko; Myojin, Tomoya; Matsuoka, Minami; Sasaki, Shoh; Uchiyama, Tomoko; Morita, Kohei; Fujii, Tomomi; Hatakeyama, Kinta; Ohbayashi, Chiho
Although it has been described that extranodal marginal zone lymphomas of mucosa-associated lymphoid tissue (MALT lymphomas) are the most common type among primary salivary gland lymphomas (SGLs), some studies revealed that the frequency of follicular lymphomas (FLs) was as high as that of MALT lymphomas. However, it has been reported that many of these FLs may have developed in lymph nodes attached to the capsule of the glands or intraglandular lymph nodes. Clinical, histological, immunohistochemical, and cytogenetic features of 11 SGL cases, which were extracted from our surgical pathology file consisting of consecutive pathology cases, were reevaluated to further characterize whether they were actually primary SGLs. There were 3 (27%) cases of FLs, 5 (46%) cases of MALT lymphomas, and 3 (27%) cases of diffuse large B-cell lymphomas. Although all of our FL cases fulfilled the criteria of primary SGL, tumors of several FL cases were surrounded by podoplanin (by D2-40)–positive elongated vessels or linear structures indicative of nodal subcapsular sinuses (open or remnant). This finding would support the aforementioned possibility, and podoplanin staining is necessary before concluding that a FL is a primary SGL.